Model Rasch Sebagai Analisis Ketepatan Instrumen Butir Soal dan Evaluasi Biologi SMA Kelas 11 - Gracia Cita Cinantya; Sugiharto Bowo (Universitas Negeri Jakarta, 2026)
Assessment is a crucial component of education, measuring student learning. Multiple-choice tests are one of the most common assessment methods, and their thorough analysis is essential to ensure fairness and accuracy. When measuring environmental literacy among high school students, the psychometric quality of the instruments must be carefully studied to ensure they truly reflect student competence. The Rasch model, a part of Item Response Theory, is a powerful tool for evaluating item quality by examining the fit of student responses to the Model's expectations and determining item difficulty. This study aimed to develop and validate an instrument to measure environmental literacy among Grade XI students using the Rasch model. The developed tool encompasses knowledge, thinking skills, attitudes, and actions related to the environment. The Point-Measure Correlation results indicated a positive relationship between student ability and their responses, although some items were identified as needing revision for improved performance. The average match between the Model's predictions and the actual student responses was 73.5%, signifying that most of the data aligned with the Model's expectations. This research provides a robust framework for the psychometric evaluation of assessment tools in science education.